Genre Diffusion Of Baricco's Works - Rasulova Munira Maratovna (Zien Journals, 2025)
This article examines the genre diffusion of Baricco’s works. As it is known, the essential parameter of any text is its belonging to a certain style and genre. However, when determining the genre of any of A. Baricco's works there are certain difficulties. The author strives to go beyond the traditional genre definition, experimenting with form and content. This has led to the emergence of new genres or subgenres, as well as the emergence of a unique artistic style. Among his works there are adventure and philosophical novels, a prose poem, a love melodrama or a thriller
Keywords: genre; genre diffusion; Italian literature